Density and distribution of cutaneous sensilla on tails of leopard geckos (Eublepharis macularius) in relation to caudal autotomy. (19th March 2014) - Russell, Anthony P.; Lai, Erica K.; Lawrence Powell, G.; Higham, Timothy E.
ABSTRACT The lizard tail is well known for its ability to autotomize and regenerate. Physical contact of the tail by a predator may induce autotomy at the location at which the tail is grasped, and upon detachment the tail may undergo violent, rapid, and unpredictable movements that appear to be, to some degree, regulated by contact with the physical environment. Neither the mechanism by which tail breakage at a particular location is determined, nor that by which environmental feedback to the tail is received, are known. It has been suggested that mechanoreceptors (sensilla) are the means of mediation of such activities, and reports indicate that the density of sensilla on the tail is high. To determine the feasibility that mechanoreceptors are involved in such phenomena, we mapped scale form and the size, density, distribution, and spacing of sensilla on the head, body, limbs, and tail of the leopard gecko. This species has a full complement of autotomy planes along the length of the tail, and the postautotomic behavior of its tail has been documented. We found that the density of sensilla is highest on the tail relative to all other body regions examined; a dorsoventral gradient of caudal sensilla density is evident on the tail; sensilla are more closely spaced on the dorsal and lateral regions of the tail than elsewhere and are carried on relatively small scales; and that the whorls of scales on the tail bear a one to one relationship with the autotomy planes. Our results are consistent with the hypotheses of sensilla being involved in determining the site at which autotomy will occur, and with them being involved in the mediation of tail behavior following autotomy. These findings open the way for experimental neurological investigations of how autotomy is induced and how the detached tail responds to external environmental input. J. Morphol. 275:961–979, 2014. © 2014 Wiley Periodicals, Inc.